Pengembangan Budaya Disiplin pada Penerapan Sholat Dhuha - Mila Santika; Afiful Ikhwan (Yayasan Letiges Konsultan Sosial, 2024)
This research aims to understand the process of developing a culture of discipline in implementing the Dhuha prayer and its impact. This study used descriptive qualitative method. Data collection was carried out by observation, conducting interviews and keeping detailed notes. Analysis uses data reduction, visualization and validation techniques. The development of a culture of discipline and implementation of Dhuha prayers is supported by a residential system. The class teacher participates in learning activities, supervises students, motivates and makes a personal approach to students, and provides the necessary equipment and materials. Methods that have been established for planning, implementing and implementing the consequences of a disciplinary culture in building student character are applied. The influence of a culture of discipline on the implementation of Duha prayers, namely through a culture of discipline students become more disciplined, more motivated and more religious.